IMPLEMENTING DIRECT METHOD BY USING GAMES TO IMPROVE EFL STUDENTS' READING COMPREHENSION - Meutia, Putri Dini; Majid, A. Halim; Nafisah, Sufiah (Fakultas Agama Islam Universitas Muhammadiyah Aceh, 2020)
Reading skill is one of the aspects of the foreign language which need to be master by the students. Thus it needed an appropriate method to improve the students' reading skills, especially reading comprehension. Therefore, the researchers conducted the study by using the Direct Method to improve reading comprehension. The purpose of this study was to find out whether the Direct Method by using games can improve the students' reading comprehension. The sample was taken from the second-year students of MAN Sibreh consisted of 25 students. The experiment was conducted in four meetings. In collecting the data, this study used pre-test and post-test as the research instruments. The pre-test was given in the first meeting while the post-test was given in the last meeting. After analyzing the data, the obtained t-score is 3,92. It indicates that there are significant differences between pre-test and post-test. Moreover, the critical value of t for the degree of freedom was 2,06 at the level significance of 5% (0,05). Thus, the t-score (3,92) is higher than the t-table (2,06). Therefore, the hypothesis is accepted.